2020
DOI: 10.1002/chem.202000302
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electrostatic Barrier of Tetrathiafulvalene Dications using a Tetra‐stable Donor–Acceptor [2]Rotaxane

Abstract: At etra-stable donor-acceptor [2]rotaxane 1·4PF 6 has been synthesized. The dumbbell component is comprised of an oxyphenylene (OP), at etrathiafulvalene (TTF), a monopyrrolo-TTF (MPTTF), and ah ydroquinone (HQ) unit, which can act as recognition sites (stations) for the tetra-cationic cyclophane cyclobis(paraquat-p-phenylene) (CBPQT 4 + ). The TTF and the MPTTF stations are located in the middle of the dumbbell component and are connected by at riethylene glycol (TEG) chain in such aw ay that the pyrrole moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…S6†). Previous studies 25 have shown that such behaviour is fully consistent with the formation of the MPTTF 2+ dication and, hence, the formation of the oxidised [2]rotaxane 2 6+ and [2]pseudorotaxane 1 ⊂CBPQT 6+ , respectively, upon addition of TBPASbCl 6 .…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…S6†). Previous studies 25 have shown that such behaviour is fully consistent with the formation of the MPTTF 2+ dication and, hence, the formation of the oxidised [2]rotaxane 2 6+ and [2]pseudorotaxane 1 ⊂CBPQT 6+ , respectively, upon addition of TBPASbCl 6 .…”
Section: Resultssupporting
confidence: 71%
“…These interlocked compounds have been used extensively and successfully to create artificial molecular machines (AMMs) 10 in an effort to mimic both biological processes (biomimetic 11 ), such as the controlled molecular motion taking place in ATP-synthase 12,13 or kinesin's ability to walk along the microtubule filament, 14 and macroscopic processes (technomimetic 11 ), such as pumps, 15–19 cars 20 and elevators. 21 These designs often rely on controlling 15,22–24 the mechanisms of stimuli-driven motion, and thus motivate studies of kinetics 25–29 and the underlying energy landscapes. 30,31 We do this here by measuring the impact of double oxidation on the barrier to the motion of a mobile ring (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations